MUSIC THEORY AND ITS DEVELOPMENT PERIODIZATION - Xusanov Rustamjon Ravshanjon o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article is based on the historical roots, basis, stages of development of theoretical musicology, the importance of theoretical musicology. Also, the theoretical and educational importance of music education in music education, music studies, music culture lessons is highlighted.